Journeys into Islamic Southeast Asia - Grand Brilliance sdn. Bhd. (Selangor : Grand Brilliance Sdn. Bhd., 2004)
contained 13 episode of Islamic history in Southeast Asia
13 episode
Journalist, Zainal Ariffin Ismail, Mohd Zailand Abd. Rahman, Muhamad Amin Yusoff; graphics, Azman Aziz, Amir awang, Rosni Mat Isa; technical producer; Mohd Zait Abd Samad, Roslan Sunal
Keywords: Islam -- Asia, Southeastern -- History; Islam -- Asia, Southeastern